4m+8+5(4m-5)-5(m+5)=0

Simple and best practice solution for 4m+8+5(4m-5)-5(m+5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4m+8+5(4m-5)-5(m+5)=0 equation:


Simplifying
4m + 8 + 5(4m + -5) + -5(m + 5) = 0

Reorder the terms:
4m + 8 + 5(-5 + 4m) + -5(m + 5) = 0
4m + 8 + (-5 * 5 + 4m * 5) + -5(m + 5) = 0
4m + 8 + (-25 + 20m) + -5(m + 5) = 0

Reorder the terms:
4m + 8 + -25 + 20m + -5(5 + m) = 0
4m + 8 + -25 + 20m + (5 * -5 + m * -5) = 0
4m + 8 + -25 + 20m + (-25 + -5m) = 0

Reorder the terms:
8 + -25 + -25 + 4m + 20m + -5m = 0

Combine like terms: 8 + -25 = -17
-17 + -25 + 4m + 20m + -5m = 0

Combine like terms: -17 + -25 = -42
-42 + 4m + 20m + -5m = 0

Combine like terms: 4m + 20m = 24m
-42 + 24m + -5m = 0

Combine like terms: 24m + -5m = 19m
-42 + 19m = 0

Solving
-42 + 19m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '42' to each side of the equation.
-42 + 42 + 19m = 0 + 42

Combine like terms: -42 + 42 = 0
0 + 19m = 0 + 42
19m = 0 + 42

Combine like terms: 0 + 42 = 42
19m = 42

Divide each side by '19'.
m = 2.210526316

Simplifying
m = 2.210526316

See similar equations:

| x^2-(2a-1)x+a^2-a+1=0 | | 0.57x^3+4x=4 | | 70x+90y=350 | | 0.2(p+6)-0.7(p+4)=-3 | | 0.57x^3+4u=4 | | 6y+12-4=-10 | | 4b^2+b-19=0 | | 3x+4(2x-3)=6 | | 2(f-9)=-24 | | 4=x^4 | | 3+2y-24=14 | | 7+3x=7x-29 | | 45=x-36 | | 6c-1=23 | | 216=5x | | -3(2t+3)=-3 | | -133=-7(6n+7) | | -2x+3(3x-6)=-2-9x | | 10(s-4)=-85 | | 2m-8=10+18 | | 3x+1y=392 | | 14x-9=11y | | 900000000000000000000000000000000+423523542546224624246426264462264264642426264426565374676585798966975685362431432134245436356457764575976980=x | | k-3(5)=12(5) | | 7-3x=x+3x | | X^2+11X+19=X-6 | | 7r+2=(5r-4) | | 8(3-5m)= | | 2(3x+3)+6(x-4)= | | 8x+17=-5(3-8x) | | 8.1-1.5x=-6.9 | | 3x^3+x^2-2=0 |

Equations solver categories